2002
DOI: 10.1212/wnl.58.7.1062
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in chronic daily headache

Abstract: In the general population, CDH reduced all QoL aspects studied with the SF-36. This reduction in QoL was most marked in subjects with analgesic overuse. QoL was affected more by the chronicity than by the intensity of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
131
1
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 23 publications
11
131
1
7
Order By: Relevance
“…Guitera et al [22] studied HRQoL by SF-36 in 89 unselected subjects from an epidemiological study in the general population who suffered from chronic daily headache (CDH) and compared HRQoL in this group with that of 89 healthy matched subjects. Of the CDH patients, 50 subjects suffered from chronic tension-type headache (CTTH), 37 had transformed migraine (TM), and two had new daily persistent headache.…”
Section: Quality Of Life In Chronic Daily Headachementioning
confidence: 99%
“…Guitera et al [22] studied HRQoL by SF-36 in 89 unselected subjects from an epidemiological study in the general population who suffered from chronic daily headache (CDH) and compared HRQoL in this group with that of 89 healthy matched subjects. Of the CDH patients, 50 subjects suffered from chronic tension-type headache (CTTH), 37 had transformed migraine (TM), and two had new daily persistent headache.…”
Section: Quality Of Life In Chronic Daily Headachementioning
confidence: 99%
“…Similarly, the relationship between length of pain and analgesics intake was significant for all the days (OR=2. [5][6][7][8][9][10][11][12][13][14], as it can be seen in Fig 2. A statistically significant relationship was not found between the items devised to measure headache related missing workdays and the golden standard (data not shown).…”
Section: Construct Validitymentioning
confidence: 99%
“…controls 5,6 . Several factors might affect the internal validity of studies in CDH patients, among them the lack of reliable measurement instruments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, patients with chronic headaches complain about signifi cant well-being impairment with damage in their quality of life 11 . Most studies have reported the consequences of migraine in the quality of life [12][13][14][15][16][17] ; few reported the quality of life of patients with CDH [18][19][20][21][22] . When compared to the general population, the patients with CDH present signifi cant reduction in all SF-36 domains 22 .…”
mentioning
confidence: 99%